2020
DOI: 10.1002/rcm.8940
|View full text |Cite
|
Sign up to set email alerts
|

Rapid quantitative screening of cyanobacteria for production of anatoxins using direct analysis in real time high‐resolution mass spectrometry

Abstract: Rationale Anatoxins (ATXs) are a potent class of cyanobacterial neurotoxins that are increasingly problematic in drinking water reservoirs and recreational water bodies worldwide. Because of their high polarity and low molecular weight, analysis of ATXs is challenging and they can be considered underreported compared with other classes of cyanobacterial toxins. Improved screening methods are therefore needed to effectively assess their occurrence and concentrations in the environment. Methods A rapid screening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…The LC – HRMS method has a LOD of 0.1 ng/mL in culture extracts and excellent resolution of the ATXs from each other ( Figure S1 ) and potential matrix interferences such as phenylalanine (Phe). 22 In order to evaluate the suitability of the FS DART method for analysis of ATXs in a more complex matrix, a preliminary set of 10 cyanobacterial field samples was analyzed by both DART – HRMS and LC–HRMS. This analysis showed that in several cases, high concentrations of ATXs were determined by DART – HRMS in the absence of detection of ATXs by LC – HRMS ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The LC – HRMS method has a LOD of 0.1 ng/mL in culture extracts and excellent resolution of the ATXs from each other ( Figure S1 ) and potential matrix interferences such as phenylalanine (Phe). 22 In order to evaluate the suitability of the FS DART method for analysis of ATXs in a more complex matrix, a preliminary set of 10 cyanobacterial field samples was analyzed by both DART – HRMS and LC–HRMS. This analysis showed that in several cases, high concentrations of ATXs were determined by DART – HRMS in the absence of detection of ATXs by LC – HRMS ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…17 , 18 High-resolution mass spectrometry (HRMS) is particularly effective at resolving ATX from its common isobaric interference phenylalanine, which can cause interference and ionization suppression in some MS-based methods. 16 , 19 21 The improved selectivity of HRMS over low-resolution MS instruments has also enabled the use of direct ionization techniques for ATX analysis including direct analysis in real time (DART), 22 matrix-assisted laser desorption ionization, 20 and laser-induced thermal desorption ionization. 21 , 23 These techniques offer the potential for higher throughput than LC–MS because of their lack of chromatographic separation and reduced requirement for sample preparation but also pose challenges in selectivity and matrix effects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DART-MS has been a popular choice for the analysis of water samples, and was recently applied to the detection of anatoxins, a type of cyanobacterial neurotoxins sometimes found in drinking water reservoirs. 112 and clay, containing 11 different PFAS compounds. 115 The method was first validated using materials spiked with analytical standards before being tested with genuine soil samples collected from an aqueous film forming foams site.…”
Section: Environmentalmentioning
confidence: 99%